2011
DOI: 10.3989/scimar.04352.15a
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of spear fishing by using competitions records and underwater visual censuses

Abstract: Summary:Recreational fishers are increasingly competing for space and resources with commercial fishers worldwide, but have been poorly studied. In particular, the impacts of spearfishing competitions on the temperate fish assemblages have seldom been analysed. In Galicia (NW Spain), there are currently 5000 spear fishers, and 500 of them participate in spearfishing competitions. An historic archive of spearfishing competitions was used to assess their influence on the subsequent competitions in the area and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…ecosystem health, composition of the typical coastal fish community) influence the comparison of catch characteristics (e.g. catch rate, biological and ecological indicators) between different areas and studies (Diogo & Pereira, ; Lloret et al., ; Pita & Freire, , ), the present study showed that the expertise of a fisher also contributed significantly to these differences. The hypothesis that a human effect is one of the main drivers of fishing power has been debated in the literature with some divergence.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…ecosystem health, composition of the typical coastal fish community) influence the comparison of catch characteristics (e.g. catch rate, biological and ecological indicators) between different areas and studies (Diogo & Pereira, ; Lloret et al., ; Pita & Freire, , ), the present study showed that the expertise of a fisher also contributed significantly to these differences. The hypothesis that a human effect is one of the main drivers of fishing power has been debated in the literature with some divergence.…”
Section: Discussionsupporting
confidence: 48%
“…Spearfishing is recognised for its biological impacts on costal fish communities (e.g. Lloret & Font, ; Mann et al., ; Meyer, ; Pita & Freire, ; Young, Foale & Bellwood, ). Despite the rising number of publications on spearfishing, there are still several gaps in research, and with the exception of spearfishing competitions, there are few studies that address the spearfishers’ experience.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the high catch rates achieved by some practitioners (e.g., Lloret et al., ), coupled with the main species groups sought (e.g., cephalopods, crabs, lobsters, seabreams, snappers, groupers, jacks) also being targeted by commercial and other recreational fishers (Frisch, Baker, Hobbs & Nankervis, ), has resulted in conflicts between different fishing modes around the globe. It has also led to a generalised belief that spearfishing is responsible for significant changes on particular species groups inhabiting coastal areas, such as wrasses, groupers or snappers (Coll et al., ; Cook, ; Frisch, Cole, Hobbs, Rizzari & Munkres, ; Meyer, ; Pita & Freire, ). These groups of species occur mostly within depth ranges where spearfishers operate (i.e., <25 m depth)—this, coupled with their biological characteristics (slow growing, long‐lived and late maturation), renders these species the most vulnerable to spearfishing (Lindfield, McIlwain & Harvey, ; Lloret et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Competitive spearfishers invest a considerable amount of time in physical training and fishing(Pita and Freire, 2016). Since roughly 500 spear fishers participate in competitions in the area, it is estimated that approximately 0.8% of competitive spearfishers were included in the study.…”
mentioning
confidence: 99%